Towards Achievement of SDG 6 in campus: A Sustainable Water Management Case Study from Qassim University - Mohamed, Sherif Elsayed; Hamad, Essam M.; Alnassar, Mohammed A.; Aljohani, Abdullah S.M.; Al-Harbi, Waleed Dakhel (Journal of Sustainability Perspectives, 2025)
Qassim University is in Mulaida, Qassim, Saudi Arabia. The scarcity of potable water is one of the major environmental challenges, not only in Qassim but also across most of the kingdom. Therefore, the university has adopted a water conservation program to preserve water and make it more efficient in all its facilities. To achieve this, the university implements measures and innovative technologies for the effective use of water. This includes producing drinking water from a desalination plant established by the university with the highest specifications and supplying it to the campus facilities. Additionally, wastewater treatment is carried out to ensure safe use for irrigation purposes within the university's landscaped areas. The university also rehabilitates several wells while designing and dividing irrigation zones and supervises and monitors tree planting and green areas. Furthermore, there are plans for a water recycling plant and the installation of pipelines to transport recycled water for irrigation in the university's green fields. The university buildings are also equipped with laboratories that employ neutralization methods to treat hazardous waste. The water management program at Qassim University contributes to providing advanced solutions and applications regarding the role of sustainable universities in managing water resources. Therefore, the study highlights the importance of technology and innovation in preserving and utilizing resources in higher education institutions. Qassim University serves as a good example for universities within and outside the kingdom that address water scarcity and promote sustainable practices both within and outside the campus.